1999
DOI: 10.30843/nzpp.1999.52.11601
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of <i>Venturia inaequalis</i> and <i>V. pirina</i> to dodine in New Zealand

Abstract: The sensitivity of Venturia inaequalis and V. pirina to dodine was evaluated during the 1997/98 season using EC 50 and EC 95 values for colony growth on amended agar. Seventy one orchards with known fungicide application histories were sampled in the six main apple growing districts of New Zealand and Venturia isolates were tested. Sensitivity values were 19% lower in 1998 than indicated by data from 1994. No relationship between sensitivity and orchard fungicide spray history was detected. Despite its frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
6
2
Order By: Relevance
“…However, as for the DMI fungicides, the isolates from organic orchards tended to have low EC 50 values and the isolates from orchards in which resistance management guidelines were exceeded tended to have higher EC 50 values. The overall mean EC 50 value of 0.24 mg/litre (Table 1) was lower than the values of 0.85 mg/litre reported by Bakker et al (1995) and 0.527 reported by Bakker (1999).…”
Section: Dodine Sensitivitycontrasting
confidence: 58%
See 3 more Smart Citations
“…However, as for the DMI fungicides, the isolates from organic orchards tended to have low EC 50 values and the isolates from orchards in which resistance management guidelines were exceeded tended to have higher EC 50 values. The overall mean EC 50 value of 0.24 mg/litre (Table 1) was lower than the values of 0.85 mg/litre reported by Bakker et al (1995) and 0.527 reported by Bakker (1999).…”
Section: Dodine Sensitivitycontrasting
confidence: 58%
“…As was the case for myclobutanil, isolates from the three organic orchards had amongst the lowest EC 50 values and isolates from IFP orchards that exceeded resistance management recommendations (orchards 7, 8 and 9) had relatively high EC 50 values. The overall mean EC 50 value for penconazole of 0.12 mg/litre (Table 1) was considerably higher than the national mean of 0.039 mg/litre reported by Whelan et al (Whelan et al 1992), 1993-94 (Bakker et al 1995 and 1997-98 (Bakker 1999 (1992), but was only slightly greater than the mean of 0.10 reported by Bakker et al (1995). Previous Hawke's Bay EC 50 values for penconazole were 0.033 mg/litre (Whelan et al 1992) and 0.11 mg/litre (Bakker et al 1995).…”
Section: Penconazole Sensitivitymentioning
confidence: 57%
See 2 more Smart Citations
“…A survey of Hawke's Bay apple orchards in the 2010-11 season (Beresford et al 2012) indicated that DMI sensitivity in V. inaequalis had decreased since surveys in the 1990s (Whelan et al 1992;Bakker et al 1995), to a degree where loss of black spot control could now be expected in some orchards. There was no evidence of a loss of sensitivity to dodine in Hawke's Bay since the 1990s (Bakker et al 1995;Bakker 1999).…”
Section: Introductionmentioning
confidence: 91%